Identifying Sources of Moral Distress Amongst Critical Care Staff During the Covid-19 Pandemic Using a Naturalistic Inquiry - Margaret Scott PhD; Rachel Wade MSc; Guy Tucker PhD; John Unsworth PhD (SAGE Publishing, 2023)
Introduction Moral distress can have a significant impact on the mental health and well-being of practitioners. Causes of moral distress in critical care have been identified as futile treatment, conflict between family members and staff, lack of resources, and dysfunctional teams. Objectives This study explores the sources of moral distress during the COVID-19 pandemic and the meaning that staff attached to these events. The study aims to examine whether the sources of moral distress are similar, or different, to those that commonly occur in critical care departments. Methods Naturalistic inquiry using semi-structured individual interviews with 17 participants drawn from nursing ( n  = 12), medicine ( n  = 3), and the allied health professions ( n  = 2). The interviews were recorded and transcribed verbatim. The transcripts were analyzed using reflexive thematic analysis. Results The results suggested that while there were some similar sources of moral distress including caring for dying patients and not being able to provide the usual standard of care, the nature of the disease trajectory and frequency of death had a significant impact. In addition, the researchers found that providing care which was counter-intuitive, concerns about the risks to the staff and their families and the additional burdens associated with leading teams in times of uncertainty were identified as sources of moral distress. Conclusion This study explored the potential sources of moral distress during the pandemic and the meaning that practitioners attached to their experiences. There were some similarities with the sources of moral distress in critical care which occur outside of a pandemic. However, the frequency and intensity of the experiences are likely to be different during a pandemic, with staff describing high volumes of deaths without family members present. In addition, new sources of moral distress related to uncertainty, counter-intuitive care and concerns about personal and family risk of infection were identified.